Effect of ZnO in various alcohols on photoelectric characteristics of OSC - Seisembekova, T.E.; Aimukhanov, A.K.; Ilyassov, B.R.; Valiev, D.; Zeinidenov, A.K.; Zhakhanova, A.M. (Karagandy University of the name of acad. E.A. Buketov, 2023)
The paper presents the results of a study of the effect of alcohols on the electron transport of the ETL layer of a ZnO polymer solar cell with an inverted structure. To obtain films, zinc acetate was dissolved under the same experimental conditions in isopropanol, butanol and ethanol. According to the SEM data, it was found that the use of various alcohol solvents in the synthesis of the film shows a change in the morphology of the surface. The observed changes in the interface of the surface of the films are associated with the formation of ZnO aggregates depending on the polarity used of the alcohols. It is shown that the optical width of the ZnO band gap also depends on alcohol solvents. It is shown that the aggregation of ZnO has an effect on the electron transport and efficiency of the polymer solar cell. The voltage characteristics of the solar cells FTO/ ZnO/P3HT: IC60MA/PEDOT: PSS/Ag were measured. It is shown that the smallest aggregation of ZnO is observed in Isopropanol, in which the organic cell showed the highest efficiency of converting solar energy into electrical energy. The polymer solar cell has been the efficiency 2.5 %. From the obtained ETL impedance measurement data, the ZnO based layer obtained in Ethanol has the lowest electron transport parameters. This is due to the high degree of aggregation of ZnO, as a result of which the resistance to increases of the interface ZnO/FTO. The solar cells based ZnO in Ethanol demonstrated an efficiency value of 0.9 % compared to ZnO in Butanol with an efficiency of 1.6 %.
Әр түрлі спирттердегі ZnO-нің OSC фотоэлектрлік сипаттамаларына әсері
Влияние ZnO в различных спиртах на фотоэлектрические характеристики OSC
Keywords: ZnO; Isopropanol; Ethanol; Butanol; surface morphology; thermal annealing; optical spectroscopy; impedance spectroscopy